Comparison of Antimicrobial Activity between Ethanolic Extract and Essential Oil of Ginger (Zingiber officinale) against Food-borne Bacteria - Foustine, Shania; Andre, Andre; Setiadi, Bastian; Hartiadi, Leonny Yulita; Sahamastuti, Agnes Anania Triavika (Indonesia International Institute for Life Sciences, 2019)
Background: Ginger (Zingiber officinale) is one of the most well-known spices with antimicrobial activity. However, different extraction methods of ginger will result in different antimicrobial properties due to the various substances extracted. This study aimed to compare antimicrobial activity between ethanolic extract and essential oil of ginger against food-borne bacteria grown in 2.1% Mueller Hinton agar. Methods: Fresh ginger rhizomes were extracted either by using vapor distillation method or maceration using ethanol to obtain ginger essential oils (GEO) and ginger ethanolic extract (GEE), respectively. Ethanolic extract and essential oil of ginger at different concentrations were then tested for their antimicrobial activity using disk diffusion method against Escherichia coli, Bacillus subtilis, Salmonella typhi, and Staphylococcus aureus. Tetracycline was also used as a standard of antibacterial agent. Results: Ginger essential oil in 25%, 50%, and 100% showed significant growth inhibition of four types of bacteria compared to ginger ethanolic extract. This antimicrobial effect of ginger essential oil was shown to be dose-dependent. However, it has been demonstrated that ginger ethanolic extract 50% and 100% has a stronger antimicrobial effect against B.subtilis. Conclusion: Ginger essential oil and ethanolic extract showed different degree of antibacterial activity against food-borne bacteria due to compound contained within respective extracts, with a higher degree of activity found in ginger essential oil. These may show that different ginger extract may have different antibacterial activity.